Cardiac Transplantation in HIV-Positive Patients: A Narrative Review. (1st June 2021) - Wairimu, Faith; Ward, Natalie C.; Liu, Yingwei; Dwivedi, Girish
Abstract : Abstract: Before the introduction of highly active antiretroviral therapy, patients infected with HIV experienced poor prognosis including high rates of opportunistic infections, rapid progression to AIDS, and significant mortality. Increased life expectancy after therapeutic improvements has led to an increase in other chronic diseases for these patients, including cardiovascular disease and, in particular, end-stage heart failure. Historically, HIV infection was deemed an absolute contraindication for transplantation. Since the development of highly active antiretroviral therapy, however, life expectancy for HIV-positive patients has significantly improved. In addition, there is a low incidence of opportunistic infections and the current antiretrovirals have an improved toxicity profile. Despite this, the current status of cardiac transplants in HIV-positive patients remains unclear. With this in mind, we conducted a narrative review on cardiac transplantation in patients with HIV.